A novel robotic catheter system with force and visual feedback for vascular interventional surgery. (1st January 2012) - Guo, Jian; Guo, Shuxiang; Xiao, Nan; Ma, Xu; Yoshida, Shunichi; Tamiya, Takashi; Kawanishi, Masahiko
This paper proposes a novel master-slave robotic catheter operating system with force feedback and visual feedback for vascular interventional surgery (VIS). The robotic catheter system has good manoeuvrability, it can transmit the surgeon's skill to insert and rotate the catheter and avoids danger during VIS using force and visual feedback. In addition, it can be used to train unskilled surgeons to perform VIS. We performed a simulation experiment to validate our system using an endovascular evaluator (EVE). The experimental results demonstrated that the stability and response of the system were good. The robotic catheter system is suitable for performing VIS.